Recent advancements in prebiotic oligomers synthesis via enzymatic hydrolysis of lignocellulosic biomass. Issue 2 (1st February 2022) - Saini, Reetu; Patel, Anil Kumar; Saini, Jitendra Kumar; Chen, Chiu-Wen; Varjani, Sunita; Singhania, Reeta Rani; Di Dong, Cheng
ABSTRACT: Interest in functional food, such as non-digestible prebiotic oligosaccharides is increasing day by day and their production is shifting toward sustainable manufacturing. Due to the presence of high carbohydrate content, lignocellulosic biomass (LCB) is the most-potential, cost-effective and sustainable substrate for production of many useful products, including lignocellulose-derived prebiotic oligosaccharides (LDOs). These have the same worthwhile properties as other common oligosaccharides, such as short chain carbohydrates digestible to the gut flora but not to humans mainly due to their resistance to the low pH and high temperature and their demand is constantly increasing mainly due to increased awareness about their potential health benefits. Despite several advantages over the thermo-chemical route of synthesis, comprehensive and updated information on the conversion of lignocellulosic biomass to prebiotic oligomers via controlled enzymatic saccharification is not available in the literature. Thus, the main objective of this review is to highlight recent advancements in enzymatic synthesis of LDOs, current challenges, and future prospects of sustainably producing prebiotic oligomers via enzymatic hydrolysis of LCB substrates. Enzyme reaction engineering practices, custom-made enzyme preparations, controlled enzymatic hydrolysis, and protein engineering approaches have been discussed with regard to their applications in sustainable synthesis of lignocellulose-derived oligosaccharide prebiotics. An overview of scale-up aspects and market potential of LDOs has also been provided. Graphical Abstract: uf0001